Pengambilan Data Inklinasi Dan Azimuth Dalam Proses Measurement While Drilling (MWD) Menggunakan Metode Mud-Pulse Telemetry Pada Sumur X Lapangan Y - Geusan Buana Fauzan; M.Mahlil Nasution; Citra Wahyuningrum (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2024)
The Measurement While Drilling (MWD) process is essential in the oil and gas industry to obtain real-time data during drilling operations. One of the MWD methods commonly used is mud- pulse telemetry, which transmits data through mud pulses generated by the drilling fluid. This study focuses on the data acquisition process on MWD using Mud-pulse telemetry at Well X, which is located in Field Y. The purpose of this research is to analyze the performance of the MWD system, evaluate the quality of the data obtained through mud-pulse telemetry. The results showed that from the results of well X data, Mud Pulse Telemetry with Continuous Wave System can transmit data continuously and in real time and can measure up to a depth of 1,268 meters. The advantage of Mud Pulse Telemetry is that mud pulses can transmit data with a signal without being disturbed by interference from signals inside the earth, so the resulting noise tends to be a little lack ing in it. Despite the advantages of mud pulses, there are also disadvantages. One drawback is when there is a loss of circulation. Lost Circulation is the loss of drilling mud into the formation. This study recommends actions to optimize drilling conditions and fluid properties to improve the accuracy and reliability of MWD data.